Answer:
-17.5
Step-by-step explanation:
The given function is
[tex]y = - {(6})^{x} [/tex]
We want to find the average rate of change from x=0 to x=2.
Let
[tex]f(x ) = - {(6})^{x} [/tex]
The average of change of f(x) from x=a to x=b is given by:
[tex] \frac{f(b) - f(a)}{b - a} [/tex]
So to find the average rate of change of the given function from x=0 to x=2, we substitute to get:
[tex]f(0) = - {6}^{0} = - 1[/tex]
[tex]f( 2) = - {6}^{2} = - 36[/tex]
The average rate of change is:
[tex] \frac{f(2) - f(0)}{2 - 0} = \frac{ - 36 - - 1}{2 - 0} = - \frac{35}{2} = - 17.5[/tex]